Tetrahydrobiopterin (BH4) responsiveness in neonates with hyperphenylalaninemia: a semi-mechanistically-based, nonlinear mixed-effect modeling - Trefz, Friedrich K.; Blau, Nenad (Molecular genetics and metabolism, 2015)
Neonatal loading studies with tetrahydrobiopterin (BH4) are used to detect hyperphenylalaninemia due to BH4 deficiency by evaluating decreases in blood phenylalanine (Phe) concentrations post BH4 load. BH4 responsiveness in phenylalanine hydroxylase (PAH)-deficient patients introduced a new diagnostic aspect for this test. In older children, a broad spectrum of different levels of responsiveness has been described. The primary objective of this study was to develop a pharmacodynamic model to improve the description of individual sensitivity to BH4 in the neonatal period. Secondary objectives were to evaluate BH4 responsiveness in a large number of PAH-deficient patients from a neonatal screening program and in patients with various confirmed BH4 deficiencies from the BIODEF database. Descriptive statistics in patients with PAH deficiency with 0-24-h data available showed that 129 of 340 patients (37.9%) had a > 30% decrease in Phe levels post load. Patients with dihydropteridine reductase deficiency (n = 53) could not be differentiated from BH4-responsive patients with PAH deficiency. The pharmacologic turnover model, “stimulation of loss” of Phe following BH4 load, fitted the data best. Using the model, 193 of 194 (99.5%) patients with a proven BH4 synthesis deficiency or recycling defect were classified as BH4 sensitive. Among patients with PAH deficiency, 216 of 375 (57.6%) patients showed sensitivity to BH4, albeit with a pronounced variability; PAH-deficient patients with blood Phe < 1200 μmol/L at time 0 showed higher sensitivity than patients with blood Phe levels > 1200 μmol/L. External validation showed good correlation between the present approach, using 0-24-h blood Phe data, and the published 48-h prognostic test. Pharmacodynamic modeling of Phe levels following a BH4 loading test is sufficiently powerful to detect a wide range of responsiveness, interpretable as a measure of sensitivity to BH4. However, the clinical relevance of small responses needs to be evaluated by further studies of their relationship to long-term response to BH4 treatment.